FOSSILS FROM THE AMAZON: AN ANALYSIS FROM THE GEOPATRIMONY OF SALINÓPOLIS, PARÁ, BRAZIL - Sepulvreda, Barbara Alves; Costa, Sue Anne Regina Ferreira da; Lima, Aline Maria Meiguins de (Geosaberes, 2024)
The protection of geodiversity presents possibilities for expanding conceptions about nature and culture. However, in Salinópolis (Pará) the fossil record appears to be distant from society and public policies. Therefore, this study aimed to understand the current situation of the geoconservation of Salinópolis fossils through the biases of scientific theoretical support and the perception of municipal public managers. It was possible to verify that there is an extensive collection of fossils from the Pirabas Formation, but there is a lack of dialogue between the public institutions responsible for safeguarding geoheritage and the city hall of Salinópolis. Therefore, there is a need to change conceptions about the city's fossil heritage, in order to strengthen socio-environmental relations, enabling the democratization of scientific-social relations, highlighting the collective nature of the Amazonian geo-environmental heritage.